Intercultural Teaching in the EFL Classroom : The Polish Context - Sobkowiak, Paweł (International Journal of English Studies, 2021)
The qualitative research reported in this article investigated whether and to what extent students’ intercultural competence is developed in the English language classroom at the secondary education level in Poland. In interviews teachers demonstrated their positive attitudes toward intercultural teaching and decent knowledge of the issue. However, the teachers’ narratives uncovered that they assigned the interculturality the secondary role, focusing on developing linguistic and sociolinguistic competences. The collected data revealed that students in class had very few opportunities to explore foreign cultures and compare/ contrast one culture with another. There was a lack of attention to teaching that promotes critical thinking skills among learners along with activities which foster them. However, there is insufficient evidence that teachers can currently do anything more, given the context in which they work, their constraints and lack of training and support. The findings of the current study have clear implications for curriculum designers, textbook writers and institutions in charge of teacher training - EFL syllabuses, teaching materials and teacher training should focus more on developing students’ intercultural and critical thinking skills.